IMPLEMENTING THE PEER RESPONSE TECHNIQUE TO IMPROVE THE STUDENTS’ WRITING OF A PERSONAL RECOUNT TEXT - Linda Budiarsih; Yohanes Gatot Sutapa Yuliana; Clarry Sada (International Journal of Educational Best Practices, 2023)
This classroom Action Research aims to observe the implementation of the Peer Response Technique to improve the students’ writing personal recount text and their behaviour in writing activity. The participants were the students in class VIII A of SMPN 2 Sungai Raya which consisted of 31 students. Based on the teacher’s direct observation, the students in this class faced some problems in writing a personal recount text. A mixed-method approach was used to collect the data. The observation sheet, field notes, and focus group interview were used to collect the qualitative data and the writing test was used to collect the students’ writing score as the quantitative data. Three cycles were conducted in this research where each cycle consisted of three meetings. The findings of this research have shown that the implementation of the Peer Response Technique in the writing process was effective in improving not only the students’ behaviour in writing activity but also the students’ scores in writing personal recount text. The writing activities that were done in pairs could boost the students’ confidence in writing. They could also have good communication and cooperation in every writing stage that they have to do. The feedback that the students gave to each other’s writing improved their trust and their ability to learn from others’ writing. Ultimately, the peer response could improve the students’ writing personal recount text that was proved by the improvement of the student’s writing score from cycle 1 to cycle 3.